Virtual Tourism as a Social Entrepreneurship Model for the Economic Recovery of Tourism Villages (Desa Wisata) in Bali - Wei, Li; Jun, Wang; Na, Li; Suryani, Ni Kadek (Yayasan Adra Karima Hubbi, 2025)
Tourism villages (desa wisata) in Bali have long been integral to the island’s economy, providing local communities with income through tourism activities. However, the COVID-19 pandemic severely impacted the tourism industry, prompting a need for innovative solutions to support economic recovery. Virtual tourism has emerged as a promising tool, allowing tourism villages to maintain cultural engagement and reach global audiences despite travel restrictions. This research explores the potential of virtual tourism as a social entrepreneurship model for the economic recovery of desa wisata in Bali. Using a mixed-methods approach, the study examines the effectiveness of virtual tourism initiatives in generating revenue, enhancing market reach, and empowering local communities. The research found that villages with higher levels of digital engagement saw significant increases in online visitors and revenue, with virtual tours and live-streamed events being particularly successful. However, challenges such as digital infrastructure limitations and generational divides in digital literacy were also identified. The study concludes that virtual tourism can serve as a viable and sustainable model for supporting the economic recovery of desa wisata, but requires continuous innovation, training, and community involvement to ensure long-term success.